Vertically-Coupled Microring Laser Array for Dual-Wavelength Generation - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2007)
We report the first demonstration of continuous-wave operation of a tunable, compact microring laser array based on a vertical-coupling architecture, well suited to larger-scale integration. Wavelength separation tunability from 4.9 to 6.3nm is observed.